EFEK PENGGUNAAN COGNITIVE – BEHAVIORAL PLAY THERAPY UNTUK MENURUNKAN KECEMASAN PADA ANAK YANG MENGALAMI GEJALA POST-TRAUMATIC STRESS DISORDER - Cahyadi, Andi (Widya Warta, 2017)
This aim of the research was to find the effect of Cognitive Behavioral Play Therapy on reducing anxiety in a child who gets post-traumatic a stress disorder symptom. The subject of the research was a ten-year-old boy who experienced one or more anxiety symptoms. The researcher applied the single subject design method with Interrupted Time Series Design. The data were collected by Hamilton Anxiety Rating Scale (HARS) which have been adapted into Indonesian language. The researcher applied the cognitive behavioral play therapy which was administered six meetings. The analitical descriptive and statistic table were used to describe the data and Wilcoxon the Signed Rank Test was applied on it. Based on the statistical analysis, the result showed that thit (0) < t.01 (19), strengthened the significant differences between the level of anxiety before and after the treatment. The level of anxiety became lower after the application of Cognitive Behavioral Play Therapy. Â